KEBERADAAN INSTRUKSI PRESIDEN SEBAGAI PRODUK HUKUM DI INDONESIA: Ali Marwan Hsb - admin, admin; Hariz Hamdallah, Muhammad Andika (Fakultas Hukum Universitas Islam Jakarta, 2019)
The use of the indigenous by the Governor of the Special Capital Region of Jakarta raises pros and cons. This is related to the Presidential Instruction Number 26 of 1998 on Stopping the Use of Indigenous and Non-Indigenous Terms. So that this paper will be examined in relation to the existence of presidential instructions. Based on the search, it was found that the president's instructions were not legislation. The presidential instruction is only a policy that is guiding, gives policy direction and regulates the implementation of duties and work. So that there is no type of sanction that can be given if the instruction is violated. Therefore, if later the material from the presidential instruction was deemed worthy of being maintained and still needed, it was suggested that the content material be included in the content of the law. Thus, it has more binding legal force and sanctions can be included for those who violate these provisions